Outcome after intracranial hemorrhage under dabigatran and reversal with idarucizumab versus under vitamin-K-antagonists – the RIC-ICH study - Kuklik, Nils; Hüsing, Anika; Stang, Andreas; Brinkmann, Marcus; Eschenfelder, Christoph C.; Weimar, Christian; Diener, Hans-Christoph (Frontiers in Neurology, 2023)
Background Intracranial hemorrhage (ICH) is a rare but serious side effect associated with the use of oral anticoagulants, such as dabigatran. The specific reversal agent for dabigatran, idarucizumab, is available for the management of individuals with ICH. The aim of this study was to provide real-world evidence on patients with ICH and effective treatment with dabigatran and reversal with idarucizumab in clinical routine compared to those under effective treatment with vitamin-K-antagonist (VKA). Methods Registration of Idarucizumab for Patients with IntraCranial Hemorrhage (RIC-ICH) is a non-interventional study conducted in 22 German stroke units that prospectively enrolled dabigatran patients treated with idarucizumab. Retrospective data from VKA patients served as reference population. Main objective was in-hospital mortality. Further objectives included change in bleeding volume, stroke severity, and functional status. Result In-hospital mortality was 26.7% in 15 dabigatran and 27.3% in 88 VKA patients (hazard ratio 1.00, 95% CI 0.29–2.60). In patients with bleeding volume > 60 ml, mortality was lower in the dabigatran group (N = 6, 33%) compared to the VKA group (N = 15, 67%; HR 0.24, 95% CI 0.04–0.96). No differences were observed in secondary endpoints between dabigatran and VKA patients. Conclusion These results, based on data from routine clinical practice, suggest that in-hospital mortality after idarucizumab treatment is comparable to that in patients pretreated with VKA. Due to the low precision of estimates, the results must be interpreted with caution.